Pengaruh Pemberian Insentif Dan Motivasi Kerja Terhadap Peningkatan Produktivitas Kerja Pada Perusahaan Ekspedisi J&T Sampit - Sulistiani, Ika; Syahrinullah, Syahrinullah (Forecasting : Jurnal Ilmiah Ilmu Manajemen, 2023)
In the context of PT. Surya Jaya Cargo (J&T Ekspress Sampit) which is located at Jl. MT. Haryono, Kel. Mentawa Baru Hulu, Kec. Mentawa Baru Ketapang, East Kotawaringin District, Central Kalimantan Province, this study attempts to identify and analyze the impact of giving incentives to couriers (sprinters) and providing work motivation. Qualitative methodologies and descriptive research designs were used in this study. The research data was collected through observation, interviews, literature study, and analysis. Manager of PT. Surya Jaya Cargo (J&T Ekspress Sampit) must be able to inspire and motivate its employees to work effectively, enthusiastically and thoroughly if they want to increase work productivity. The results of the study show that the provision of incentives and motivation has a positive influence on employee work productivity, this is evidenced by the provision of incentives and motivation can encourage, stimulate and drive employee enthusiasm and passion so that employee work productivity increases to the maximum and can provide success for the company.